Conduct of operations and operational discipline : for improving process safety in industry. - American Institute of Chemical Engineers. Center for Chemical Process Safety (Hoboken, N.J. : Wiley, 2011)
'Process safety management (PSM) systems are only as effective as the day-to-day ability of the organization to rigorously execute system requirements correctly every time. The failure of just one person in completing a job task correctly just one time can unfortunately lead to serious injuries and potentially catastrophic incidents. In fact, the design, implementation, and daily execution of PSM systems are all dependent on workers at all levels in the organization doing their job tasks correctly every time. High levels of Operational Discipline, therefore, help ensure strong PSM performance and overall operational excellence. This book details management practices which help ensure rigor in executing process safety programs in order to prevent major accidents'--
'Center for Chemical Process Safety'--T.p.
Includes bibliographical references and index.
Keywords: Industrial safety